Review: Fruit collapse and heart rot disease in pineapple: Pathogen characterization, ultrastructure infections of plant and cell mechanism resistance (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Cano-Reinoso DM, Soesanto L, Kharisun, Wibowo C. 2021. Review: Fruit collapse and heart rot disease: Pathogen characterization, ultrastructure infections of plant and cell mechanism resistance. Biodiversitas 22: 2477-2488. Fruit collapse and bacterial heart rot are diseases in pineapple caused by Erwinia chrysanthemi (later classified as Dickeya zeae) which are increasingly prevalent in the last decade, causing devastating production loss in pineapple cultivation. Yet, comprehensive knowledge to tackle such diseases is limited, understandably due to the relatively new emerge of the diseases. Here, we review the causes of bacterial heart rot and fruit collapse, stages of infection, typical symptoms and the occurrence of resistance mechanisms in plants. In pineapple, the fruit collapse is noticeable by the release of juice and gas bubbles, also the shell of the fruit that turns into olive-green. Meanwhile, bacterial heart rot is characterized by water-soaked zones on the leaves, the formation of brown streaks on the lamina and in the mesophyll, and light-brown exudate in the blisters. The most common means of penetration into the host plant used by this type of pathogen is through plant natural openings, injuries and wounds, and entire surfaces. Concurrently, plants and fruits develop disease-resistant mechanisms to inhibit infection growth under this pathogenic attack. These mechanisms can be divided into hypersensitive reactions, locally acquired resistance, and systematic acquired resistance. In addition, pathological infections produce an interaction of the cell wall with pectolytic enzymes. Understanding the membrane breakdown process carried out by these enzymes has become critical to a pineapple protection plan. This review suggests that future research to tackle fruit collapse and bacterial heart rot can be focused on disease-resistant mechanisms, and their effects on the cell wall status with an enzymatic characterization.
Keywords: Cell wall; Dickeya; Erwinia chrysanthemi; low-acid; pectate lyase